Characterizing the distribution of selected PBDEs in soil, moss and reindeer dung at Ny-Ålesund of the Arctic. (October 2015) - Wang, Zhen; Na, Guangshui; Ma, Xindong; Ge, Linke; Lin, Zhongsheng; Yao, Ziwei
Highlights: Selected PBDEs in soil, moss and reindeer dung are investigated at Ny-Ålesund. Distribution in soil, moss and dung correlates with physicochemical properties. Significant linear relationship was observed between log Q SM and log p ° L . Abstract: Distribution of 12 selected polybrominated diphenyl ethers (PBDEs) was characterized in soil, moss and reindeer dung samples collected simultaneously at Ny-Ålesund of the Arctic. The average PBDE concentrations were 42 pg/g (dry weight) in soil, 122 pg/g in moss and 72 pg/g in reindeer dung. Significant log/log-linear relationship was observed between the soil/moss quotients ( Q SM ) and the sub-cooled liquid vapor pressures of PBDEs ( r 2  = 0.80). Moreover, excellent log/log-linear relationships between Q SM and the octanol/air partition coefficients as well as between the moss/dung quotient ( Q MD ) and the octanol/water partition coefficients of PBDEs were also observed, indicating that the physicochemical properties of PBDEs are appropriate parameters for characterizing the distribution of PBDEs in soil, moss and reindeer dung at Ny-Ålesund. Capsule abstract : Significant log-linear correlations were observed between physicochemical properties of PBDEs and their soil/moss (moss/dung) quotients.